INTEGRASI HUKUM ISLAM DAN HUKUM POSITIF DALAM DISPENSASI KAWIN: ANALISIS YURISPRUDENSI ATAS ALASAN KHAWATIR ZINA DI PENGADILAN AGAMA TASIKMALAYA - Thoriq Rahmat Amrullah; Muhsan Syarafuddin (LPPM STAI Muhammadiyah Probolinggo, 2026)
Marriage through the process of marriage dispensation on the grounds of concern about adultery is still a social phenomenon in the Tasikmalaya Religious Court. This condition shows the tension between Sharia values, which emphasize the prevention of adultery and positive law, which prioritizes protection of children from the negative effects of early marriage. This study aims to analyze the application of marriage dispensation from the perspective of Islamic law and positive law. This study uses a qualitative method with a normative-empirical juridical approach through analysis of court decisions and in-depth interviews with judges. The results show that the practice of marriage dispensation due to concerns about adultery in the Tasikmalaya Religious Court reflects the integrative application of Islamic law and positive law. The reason of “concerns about adultery” can be taken into consideration, but can only be considered urgent if proven legally through valid documents or statements. From an Islamic law perspective, judges apply the principle of maqasid al-syari'ah to prevent harm, while positive law is guided by the Marriage Law and PERMA Number 5 of 2019, which emphasizes best interests of the child. Thus, the judges' decisions reflect contextual ijtihad oriented towards justice, benefit, and legal protection for children.